Les - skladišče ogljika - Lipušček, Igor (Zbornik gozdarstva in lesarstva, 2003)
The article examines the global movement of carbon dioxide, the most important greenhouse gas due to its large quantities. We studied the carbon cycle with possibilities of its extension, and analysed the mechanisms that remove carbon dioxide from the atmosphere and bind it into solid substances for a longer period of time. The focus was on carbon dioxide sink into biomass and carbon deposit in wood. On the basis of wood component data and chemical analysis of the components, we calculated the share of carbon in wood and the equivalent quantity of carbon dioxide used in the process of photosynthesis for formation of 1.0 kg of wood matter. It was established that in the process of photosynthesis, approximately 1.8 kg of carbon dioxide is used on average from the atmosphere to form 1 kg of absolutely dry wood.
Keywords: les; ogljikov dioksid; ogljikov krog